Pengaruh Kepuasan Kerja Terhadap Produktivitas Karyawan Pada PT. Mutiara Mulia Raya (MMR) Tenggarong Seberang - Rivky Firdianto; Askiah Askiah; Sofia Ulfa Eka Hadiyanti (Journal of Innovative and Creativity, 2025)
This study aims to analyze the effect of job satisfaction on employee productivity at PT. Mutiara Mulia Raya. The background of this research is based on the importance of human resources (HR) in achieving organizational success, especially in an era of increasingly intense business competition. Employee job satisfaction is expected to enhance motivation and performance, which in turn has a positive impact on company productivity. The research method used is a quantitative approach, with data collected through questionnaires distributed to 91 employees. The analysis results show that job satisfaction has a positive and significant effect on work productivity, with a regression coefficient value of 0.293 and a significance level of 0.000. In addition, the coefficient of determination (R²) indicates that 40.3% of the variation in work productivity can be explained by job satisfaction, while the remaining percentage is influenced by other factors. This study provides recommendations for company management to continuously improve employee job satisfaction in order to encourage better productivity.